(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This study explores the concept of "textual authority" through an interpretive comparison between two distinct approaches in Islamic thought: the traditional Imami (Shi‘i) methodology, which bases the understanding of the Qur’an on the infallible authority of the Prophet’s family (Ahl al-Bayt), and the modern hermeneutic approach represented by Nasr Hamid Abu Zayd, who views the text as a cultural product shaped by its historical and social context, with the reader playing a central role in constructing its meaning. The research is structured around four main sections: the epistemological basis of Imami interpretation, the concept of textual authority in the Imami school, Abu Zayd’s thesis on the historicity of the text and the reader’s role, and finally a comparative analysis. The study concludes with a balanced critical evaluation, highlighting the strengths and limitations of each approach, and proposes the possibility of a reconciliatory interpretive dialogue that preserves the sanctity of the text while engaging with modern methodologies.